Features of EDM of mild steel with Ta-Cu powder compacted electrodes - Khan, Ahsan Ali; Mohd Hambiyah, Mohammad Azhadi; Nazi Nadin, Mohd Faiz (International Islamic University Malaysia, 2011)
Abstract. During EDM work surface roughness can be influenced by using powder compacted electrodes. The present study shows that surface roughness of workpiece is higher when using TaC/Cu green compacted electrode compared to that produced by pure copper electrode. When using TaC/Cu green compacted electrode, more material is deposited on the workpiece surface and a thick layer is formed on the surface. In addition, the particles from the electrode are randomly deposited on the workpiece surface. On the contrary, there will be only a very thin layer of material from electrode will be deposited on the workpiece surface when using pure copper electrode. A thick deposited layer with randomly deposited particles will create rougher surface rather than a thin layer. That is why surface roughness is high when using TaC/Cu green compacted electrode.